EXPLORING THE DYNAMICS OF TEACHER–STUDENT ENGAGEMENT THROUGH TRANSLANGUAGING IN EFL CLASSROOMS - Rifka Rahmita; Erna Andriyanti (Universitas Muhammadiyah Makassar, 2026)
Translanguaging has been widely recognized as a pedagogical practice enabling flexible language use in multilingual EFL classrooms; however, its role in shaping teacher–student engagement remains insufficiently explored, particularly in the Indonesian EFL context. Addressing this gap, this study investigates how teachers employ translanguaging strategies to foster engagement and how both teachers and students engage in translanguaging practices. Using a descriptive exploratory qualitative design, the study involved two English teachers and two tenth‑grade classes at a bilingual senior high school. Data were collected through classroom observations and semi‑structured interviews and analyzed using classroom discourse analysis and thematic analysis, with methodological triangulation applied to enhance credibility. The findings show that teachers employ several translanguaging strategies, including translation, collaborative dialogue, collaborative grouping, project‑based learning, inner speech, multilingual writing, word walls, sentence starters, alternating language and media, and translanguaging in speaking and writing. These practices support students’ comprehension, critical thinking, and cross‑linguistic meaning‑making, while fostering multidimensional engagement among teachers (cognitive, emotional, and social) and students (behavioral, emotional, and cognitive). By foregrounding engagement as a central analytical lens, this study demonstrates that translanguaging extends beyond linguistic scaffolding to mediate interaction and participation in EFL classrooms, highlighting its pedagogical value for engagement‑oriented EFL instruction.